The Changing Contours of Russia-India Defense Engagement - Vasily Kashin (Vestnik MGIMO-Universiteta)
The article examines the evolution of Russian defense industrial and economic policies during the military conflict in Ukraine, and the potential impact of these changes on Russian-Indian cooperation. The conflict has led to major reassessment of the defense industrial policies around the world, which is anticipated to affect Asia as well. In Russia, the conflict has prompted a long-term trend towards greater militarization of the economy. In this new context, there is a growing prospect for joint RussianIndian initiatives aimed at promoting defense industrialization projects in India, enhancing self-reliance, and bolstering India's economic mobilization potential. The most promising area of cooperation between Russia and India may not be limited to the sales of small numbers of selected high-tech weapons. Rather, it may involve creating a new industrial base to help India achieve defense self-sufficiency and be ready for economic mobilization. India's current favorable position in global politics may enable it to obtain Russian cooperation in this field on very favorable conditions. However, such a path may invite growing opposition from the US and the EU towards the IndianRussian cooperation. It is worth noting that such pressure has been present constantly, especially since 2014, but has been ineffective so far.